Acute myocardial infarction in a young man with large left ventricular thrombus and the antiphospholipid syndrome - Ayan, Mohamed (Proc (Bayl Univ Med Cent), 2018)
Antiphospholipid syndrome is an autoimmune disorder that presents clinically with venous and/or arterial thrombosis and can affect any organ. Coronary artery involvement and left ventricular thrombus are rare presentations. We report the case of a 23-year-old male smoker with a strong family history of premature coronary artery disease who presented with acute anterolateral ST elevation myocardial infarction and large left ventricular thrombus. He was treated with primary percutaneous coronary intervention with thrombectomy without stenting. He was later diagnosed with antiphospholipid syndrome.